Adenosine Signaling in Autoimmune Disorders - Giulia Magni; Stefania Ceruti (MDPI AG, 2020)
The molecular components of the purinergic system (i.e., receptors, metabolizing enzymes and membrane transporters) are widely expressed in the cells of the immune system. Additionally, high concentrations of adenosine are generated from the hydrolysis of ATP in any "danger" condition, when oxygen and energy availability dramatically drops. Therefore, adenosine acts as a retaliatory metabolite to counteract the nucleotide-mediated boost of the immune reaction. Based on this observation, it can be foreseen that the recruitment with selective agonists of the receptors involved in the immunomodulatory effect of adenosine might represent an innovative anti-inflammatory approach with potential exploitation in autoimmune disorders. Quite surprisingly, pro-inflammatory activity exerted by some adenosine receptors has been also identified, thus paving the way for the hypothesis that at least some autoimmune disorders may be caused by a derailment of adenosine signaling. In this review article, we provide a general overview of the roles played by adenosine on immune cells with a specific focus on the development of adenosine-based therapies for autoimmune disorders, as demonstrated by the exciting data from concluded and ongoing clinical trials.